Preparation of Poly(Ethylene-Co-Dicyclopentadiene) Copolymers and a Study on Their Post-Polymerization Epoxidation - Rabagliati-Canessa, F (2013)
The copolymerization of ethylene with dicyclopentadiene (DCP) using the metallocene catalyst rac-dimethylsilylbis(indenyl)zirconium dichloride (Me 2Si(Ind)2ZrCl2) proceeds with high activity producing materials with DCP incorporations of 0.5-2.7 mol%. The residual olefin moiety of the DCP comonomer is still available for reaction following polymerization and was epoxidized using H2O2 and formic acid. This reaction was optimized and proceeds with good conversion and the resulting materials show increased physical properties compared to the untreated copolymers. © 2012 Springer-Verlag.